2020
DOI: 10.1016/j.ejvs.2019.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Outcomes of Open and Endovascular Repair of Ruptured Abdominal Aortic Aneurysm in Patients with Hostile vs. Friendly Aortic Anatomy

Abstract: Observational data from national and international registries have shown that endovascular repair carries a lower peri-operative mortality risk than open repair for ruptured abdominal aortic aneurysm (AAA). Patient selection may explain the superiority of endovascular aneurysm repair (EVAR), with hostile aortic anatomy being a confounding factor. This study is a meta-analysis of outcomes in patients with hostile vs. friendly aortic anatomy treated for ruptured AAA. It was found that patients with hostile aorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 37 publications
0
16
0
1
Order By: Relevance
“…Analyses of earlier versus later cohorts show that outcomes have improved in recent years for both EVAR and OSR [ 310 , 311 ]. High mortality rates of unsuccessful EVAR for rAAA suggest that anatomical suitability and not hemodynamic condition should be the pivotal factor in choosing the surgical method for rAAA repair [ 251 , 312 , 313 ].…”
Section: Diagnosis and Managementmentioning
confidence: 99%
“…Analyses of earlier versus later cohorts show that outcomes have improved in recent years for both EVAR and OSR [ 310 , 311 ]. High mortality rates of unsuccessful EVAR for rAAA suggest that anatomical suitability and not hemodynamic condition should be the pivotal factor in choosing the surgical method for rAAA repair [ 251 , 312 , 313 ].…”
Section: Diagnosis and Managementmentioning
confidence: 99%
“…Although previous studies have confirmed that hostile aneurysm anatomy is associated with worse outcomes after EVAR, the relative importance of these "hostile factors" and any changes in their prevalence over time has remained undefined. 27,28 Finally, we found that an elevated INR and heart rate (>110 bpm) were significantly associated with greater 30-day mortality after repair, even after adjustment for the HRS and surgical repair type. Potential modification of the HRS remains a topic of ongoing research.…”
Section: Discussionmentioning
confidence: 63%
“…Perioperative mortality can be affected by a plethora of variables such as pre- and post-operative factors, anatomical factors and operative factors. 24 Propensity-matching patients on a 1:1 basis can significantly reduce the effect of these variables, which most included studies did in this meta-analysis. The study by Saqib et al 19 propensity-matched on a 1:3 basis due to a small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Aortic morphology has been suggested as an important factor in determining perioperative outcomes. 24 Aneurysmal neck length has been found to be a key predictor of mortality. 3,30 This study was unfortunately unable to explore this further due to the limitations in the databases.…”
Section: Limitationsmentioning
confidence: 99%